Cyanogenic Potential of Roasted Cassava (Manihot esculenta Crantz) roots Rale from Inhambane Province, Mozambique - L. Tivana; J. Da Cruz Francisco; B. Bergenståhl; P. Dejmek (Czech Journal of Food Sciences, 2009)
Roasted cassava roots flour is part of a common meal in Africa, it is known as rale in Mozambique. Fifty six samples of rale were collected from homes and markets in Inhambane Province, Mozambique, for cyanogenic potential (CNp) analyses. The names of cassava varieties used for preparing the rale samples could be determined in the home-collected samples, three varieties were recorded. Xinhembwe variety gave rale samples with 30 ± 8 mg CNp/kg (mean + standard error), Precoce de angola with 43 ± 11 mg CNp/kg and Rungo sabonete with 58 ± 22 mg CNp/kg dry weight. The mean cyanogenic value for all the 56 samples collected was 41 ± 16 mg CNp/kg. Cyanogenic potentials in all the rale samples were above 10 mg HCN/kg, the value regarded by the Codex Alimentarius Commission of the FAO/WHO as safe.